Influence of COL2A1-G1405S polymorphism on mandibular skeletal malocclusions: A genetic association study and in silico analysis. (October 2022) - Kalmari, Amin; Arash, Valiollah; Colagar, Abasalt Hosseinzadeh
Abstract: Objective: The current study aimed to assess the association between collagen type II alpha 1 chain ( COL2A1 ) single nucleotide polymorphism (SNP: rs2070739; C>T; G1405S) and mandibular skeletal malocclusions in the population of Mazandaran (North Iran). Design: During 13 months, 102 control samples, 81 samples with skeletal Class III malocclusion contributed by mandibular prognathism and 82 samples with skeletal Class II malocclusion contributed by mandibular retrognathism were screened. Cephalometric analysis was performed to determine the type of abnormalities. COL2A1-G1405S genotyping was performed using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. The HOPE tool was used to investigate the effect of COL2A1-G1405S on the three-dimensional structure of protein. Results: Results showed that there is no significant correlation between genotypes and alleles related to COL2A1-G1405S and mandibular prognathism (CT genotype: p -value= 0.210; T allele: p -value= 0.222). On the other hand, an association was observed between COL2A1-G1405S and mandibular retrognathism (CT genotype: p -value= 0.008; T allele: p -value= 0.011). The outputs of the HOPE tool also showed that COL2A1-G1405S can disrupt the NC1 domain of the protein. Conclusions: Here, we provide evidence that COL2A1-G1405S polymorphism may have positive correlation with the risk of skeletal Class II malocclusion contributed by mandibular retrognathism in the population of Mazandaran. Given that the COL2A1-G1405S occurs in NC1 domain, it is possible that this domain plays an important role in signaling pathways related to ossification. So, we suggest that the study of COL2A1 SNPs can help researchers understand the significant role of this collagen in mandibular skeletal malocclusions. Highlights: COL2A1-G1405S polymorphism may be associated with mandibular retrognathism. Our findings strongly linked the science of dentistry with molecular biology. COL2A1 could be used as a biomarker for studies on mandibular skeletal malocclusions.